Decolonializando o curriculo escolar através de narrativas: uma proposta de trabalho com lendas indígenas Tabajara em perspectiva intercultural critica - Silva, Rafaella Félix da (2023)
This qualitative work emerged from our concern, as non-indigenous and Portuguese language teachers, to think about ways to contribute to the process of decoloniality in schools that serve indigenous and non-indigenous students. To this end, we seek to reflect on how we can work in PL classes on sharing ancestral knowledge that serves as an essential mechanism for preserving memory and as a mechanism for reflecting on practices to strengthen identity. The Triangular Action-Research method was used, which occurred through an interview carried out with Cacique Carlinhos from Aldeia Barra de Gramame in Conde/PB to collect mythical narratives and subsequent retextualization, questionnaires, field classes carried out with 6th grade students year A of the Municipal Elementary School Professor Lina Rodrigues do Nascimento - Conde/PB and observations made by the research teacher throughout the stages of application of this research. The general objective of this work is to recognize/understand the potential of Tabajara narratives for the construction of a decolonial school curriculum. To this end, our specific objectives are (a) to have contact with local, temporal and situational narratives through Tabajara indigenous mythical narratives; (b) recognize the Eurocentric colonial thinking that still exists at school, (c) reflect on new pedagogical practices that aim to decolonialize knowledge and d) contribute to the integration of cultures in the school environment in Portuguese language classes. Based on the recognition of the coloniality present in the curriculum, our intervention proposal is to insert into the Conde/PB curriculum the study of the region's original ethnic group, the Tabajara, through the study of indigenous legends, as suggested by the National Common Curricular Base in its ability. (EF67LP28). The starting point was the concepts of relational, functional and critical interculturality (Walsh, 2009, 2012, 2022), problematizing the abyssal lines (Santos, 2009) and discussing social and educational practices capable of breaking with the rhetoric of multiculturalism and, effectively, experiencing a decolonial pedagogy through critical interculturality. To apply critical interculturality, the narratives of the Tabajara people were observed through the collection of their mythical narratives based on the perspectives of Souza (2020) and Delgado (2003). The retextualization of mythical narratives followed the thoughts of Marcuschi (2010) and Travaglia (2007) to observe that such narratives preserve ancestral knowledge (Thiél, 2013). In schools, work with critical interculturality can be done through decolonial pedagogical practices in an interdisciplinary way (Fazenda, 1994) and in Portuguese language classes, work with these narratives from this perspective can take place following Applied Linguistics (Moita Lopes, 2009).